Simple question, simple answer

Calculus Level 3

0 ( { x } ) x d x = ? \large \int_0^\infty (-\{ x \} )^{\lfloor x \rfloor} \, dx = \ ?

Notation :

  • { x } \{ x\} denote the fractional part of x x .

  • x \lfloor x\rfloor denote the floor function.

ln ( 5 ) \ln(5) ln ( 3 ) \ln(3) ln ( 2 ) \ln(2) ln ( 4 ) \ln(4)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Function { x } \{x\} is same on every interval ( n , n + 1 ) (n,n+1) , where n n is an integer, and function x \lfloor x\rfloor is constant and equal to n n on every interval ( n , n + 1 ) (n,n+1) where n n in an integer.It's easy to see that on interval ( 0 , 1 ) (0,1) , x = { x } x=\{x\} . Because of this we can write the integral as:

0 ( { x } ) x = r = 0 0 1 ( x ) r d x \int_0^\infty (-\{ x \} )^{\lfloor x \rfloor}=\sum_{r=0}^{\infty}{\int_{0}^{1}{(-x)^r dx}}

Now by evaluating this easy polynomial integral we get:

0 ( { x } ) x = r = 0 ( 1 ) r r + 1 \int_0^\infty (-\{ x \} )^{\lfloor x \rfloor}=\sum_{r=0}^{\infty}{\frac{(-1)^r}{r+1}}

Now we evaluate the sum by writing it as:

r = 0 ( 1 ) r r + 1 = lim n ( k = 1 n ( 1 2 k 1 1 2 k ) ) = lim n k = 1 n ( ( 1 2 k 1 + 1 2 k ) 2 k = 1 n 1 2 k ) = \sum_{r=0}^{\infty}{\frac{(-1)^r}{r+1}}=\lim_{n \to \infty}{(\sum_{k=1}^{n} ( \frac{1}{2k-1}-\frac{1}{2k} ) )}=\lim_{n \to \infty}{ \sum_{k=1}^{n} (( \frac{1}{2k-1}+\frac{1}{2k} ) - 2 \sum_{k=1}^{n} \frac{1}{2k}} )=

= lim n ( k = 1 2 n 1 k k = 1 n 1 k ) = lim n k = n + 1 2 n 1 k =\lim_{n \to \infty}{ (\sum_{k=1}^{2n} \frac{1}{k} - \sum_{k=1}^{n} \frac{1}{k})} = \lim_{n \to \infty}{\sum_{k=n+1}^{2n} \frac{1}{k}}

This sum can be covered to an integral:

lim n k = n + 1 2 n 1 k = lim n k = 1 n 1 n + k = lim n k = 1 n 1 1 + k n 1 n = 0 1 d x x + 1 = ln 2 \lim_{n \to \infty}{\sum_{k=n+1}^{2n} \frac{1}{k}}=\lim_{n \to \infty}{\sum_{k=1}^{n} \frac{1}{n+k}}=\lim_{n \to \infty}{\sum_{k=1}^{n} \frac{1}{1+\frac{k}{n}}}\frac{1}{n}=\int_{0}^{1}{\frac{dx}{x+1}}=\ln2

And finally we have:

0 ( { x } ) x = ln 2 \displaystyle {\int_0^\infty (-\{ x \} )^{\lfloor x \rfloor}=\ln2}

Jitendra Jain
Nov 16, 2015

opening in intervals of 1 and puting limit we get te very known series of log2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...